Implementasi Hukum Ekonomi Syariah dalam Masyarakat Multikultural di Indonesia - Hamdanil Hamdanil; Hebby Rahmatul Utamy; Bagus Pria Alwadipa; Mufti Fahrizal Harahap; Edy Saputra; Diana Farid (Pusat Riset dan Inovasi Nasional, 2025)
This paper aims to find out the implementation of sharia economic law in a multicultural society in Indonesia with its principles. The writing uses the library research method (literature study). The results obtained are that multiculturalism appreciates cultural, ethnic, and religious diversity as assets that enrich society, but brings challenges such as social tensions, economic integration, and inclusive policies. With intercultural dialog, multicultural education, and fair policies, society can overcome these challenges to create harmony and equality for all. Islamic economic principles prioritize justice in wealth distribution and transparency in trading activities, as exemplified by the Prophet Muhammad. Its modern implementation, such as in sharia-based financial institutions, supports multicultural communities through inclusive financing and is based on the values of honesty and trustworthiness.